An Ice Drift Measurement in Western Parry Channel - Verrall, R.I.; Ganton, J.H.; Milne, A.R. (ARCTIC, 1974)
A description is given of the drift of ice in Western Parry Channel during the spring and summer of 1970. Ice-buoys, planted in the fast ice of this region in April 1970, were located at approximately two-week intervals by Canadian Forces aircraft overflights. The ice in M'Clure Strait drifted to the west, whereas in Viscount Melville Sound the ice drift seemed to have no definite trend. The drift after the middle of July, when the ice was broken was compared to the ice motion calculated using Zubov's rule. The comparison yields a respectable agreement. Also, information pertaining to the longevity of ice-buoys in both polar and winter ice is given.